Hypoxic‐ischemic brain injury and narcotic drugs administration. Issue 2 (28th June 2020) - Xiong, Liu‐Lin; Zhou, Hong‐Su; Li, Ting‐Ting; Xiao, Qiu‐Xia; Zhu, Zhao‐Qiong
Abstract : Following cerebral ischemia and hypoxia, disorders in brain metabolism, histological pathology, and neural function commonly could result in different nerve injuries, to some degree. Many researchers have revealed that some narcotic drugs hold a prominent effect of prevention and therapy on cerebral ischemic‐hypoxic injury and ischemia‐reperfusion injury. However, the underlying mechanism is largely unknown. In this paper, we summarized narcotic drugs' roles in antagonizing the neurotoxicity of excitatory amino acid, reducing excitatory injury and activating intracellular signaling cascade channel, adjusting the balance of Ca 2+, increasing the expression of protective genes, reducing the generation of NO and free radical and anti‐lipid peroxidation, and discussed and elucidated their relations.